2008
DOI: 10.1071/ah080034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of current practice: compliance with osteoporosis clinical guidelines in an outpatient fracture clinic

Abstract: Better detection and management of osteoporosis will reduce unnecessary health expenditure. A number of high quality guidelines are available to support early detection and best practice management of osteoporosis in hospital settings. However, sustainable implementation of guidelines poses practical issues in terms of structure and processes in hospitals. This paper describes an investigation into guideline compliance in one large tertiary metropolitan hospital and discusses practical elements of guideline im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Thus, this level of sustained success in implementing a multidisciplinary guideline highlights how a planned approach to understanding stakeholder perspectives, philosophies and potential for change can be a powerful driver for change. Despite the disappointing baseline audit findings, 19 the follow-up audits demonstrated that targeted guideline implementation could have a dramatic effect on key indicators, including the identification of patients with likely osteoporosis, and referral by hospital staff to appropriate care, as indicated by the guidelines. This suggests that the immediate guideline implementation phase significantly influenced behaviours of staff, and that the sustained improvement, albeit at a slower rate, demonstrated continuous improvement in behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, this level of sustained success in implementing a multidisciplinary guideline highlights how a planned approach to understanding stakeholder perspectives, philosophies and potential for change can be a powerful driver for change. Despite the disappointing baseline audit findings, 19 the follow-up audits demonstrated that targeted guideline implementation could have a dramatic effect on key indicators, including the identification of patients with likely osteoporosis, and referral by hospital staff to appropriate care, as indicated by the guidelines. This suggests that the immediate guideline implementation phase significantly influenced behaviours of staff, and that the sustained improvement, albeit at a slower rate, demonstrated continuous improvement in behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,[20][21][22][23] Based on our knowledge of current performance in the hospital site, 19 we not only identified opportunities for improvement, but also ways in which improvement could occur. Then we made a concerted effort over 6 months from August 2006, to increase awareness of, and compliance with, the osteoporosis guideline recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations